2003
DOI: 10.1046/j.1365-2036.2003.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparative trials of the efficacy of proton pump inhibitors in the management of gastro‐oesophageal reflux disease and peptic ulcer disease

Abstract: Summary Background : Five proton pump inhibitors are now available for use in North America. Claims of differences in the clinical efficacy of different strengths and/or agents have been made. Aim : To identify any consistent evidence of differences in outcomes between agents or doses within this class of drugs. Methods : A search of the medical literature was performed in two electronic databases, and randomized controlled trials of higher quality were included in the assessment. Results and conclusions : Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 46 publications
1
47
0
3
Order By: Relevance
“…[4][5][6][7] The literature review showed that the PPIs are a particularly well-tolerated class of drugs. Using this evidence, the DUEC concluded that all PPIs were therapeutically equivalent in efficacy and safety.…”
Section: Description Of the Pharmacy Benefit And Interventionsmentioning
confidence: 99%
“…[4][5][6][7] The literature review showed that the PPIs are a particularly well-tolerated class of drugs. Using this evidence, the DUEC concluded that all PPIs were therapeutically equivalent in efficacy and safety.…”
Section: Description Of the Pharmacy Benefit And Interventionsmentioning
confidence: 99%
“…In the maintenance treatment of peptic ulcer it has been found that low doses of PPI have similar effects to standard doses (79). In healing rates of ulcers there are not statistically significant differences between omeprazole, pantoprazole, lansoprazole and rabeprazole (80).…”
Section: Clinical Differences Between Ppismentioning
confidence: 98%
“…Low doses of PPI compared with standard doses are not equally effective in healing erosive esophagitis or symptomatic GERD (79). However, in maintenance treatment of GERD there is similar efficacy.…”
Section: Clinical Differences Between Ppismentioning
confidence: 98%
“…There is a linear relationship between the degree of acid suppression measured by the time per day that gastric pH is higher than 4, and the healing kinetics of esophagitis [49] . With regard to the healing rates of reflux esophagitis after 4 and 8 wk, no differences are to be seen between the standard doses of the racemic PPIs (omeprazole 20 mg, lansoprazole 30 mg, pantoprazole 40 mg, rabeprazole 20 mg) [46,47] , nor did doubling the individual dose (e.g. lansoprazole 60 mg, pantoprazole 80 mg) increases efficacy.…”
Section: Initial Therapy Of Erdmentioning
confidence: 98%
“…Racemic PPIs (omeprazole, lansoprazole, pantoprazole, rabeprazole) differ in such pharmacokinetic characteristics as bioavailability and the rapidity with which an effect occurs. This, however, is irrelevant for the healing of esophagitis at 4 and 8 wk [46,47] , although the substances do differ in terms of the time required to eliminate symptoms. In a large randomized, controlled study involving more than 3 500 patients with erosive esophagitis, lansoprazole 30 mg o.d.…”
Section: Initial Therapy Of Erdmentioning
confidence: 99%